Democratizing didactic transposition: Negotiations between learners and their teacher in a secondary school - Dario Luis Banegas (Universidad de La Sabana, 2014)
Didactic transposition is a concept not usually found in TESOL but common to the teaching of subjects and languages such as French or Spanish. This term refers to the pedagogic transformations that occur between knowledge of reference and school knowledge. This article examines how such a process of transformations was democratized by engaging a group of secondary school learners to suggest topics, sources of input, and activities for the development of language-driven CLIL (Content and Language Integrated Learning) lessons. Through action research, an EFL (English as a Foreign Language) teacher in Argentina developed lessons and materials during one school year following the learners' suggestions and evaluation. Data were gathered through class interviews, surveys, and the teacher-researcher's own research journal. The experience shows that didactic transposition inscribed in sociocultural theory may become a democratic act when (1) teachers and learners not only negotiate topics and materials but, more importantly, discuss their motivations, needs, and interests and (2) teachers create spaces to incorporate learner voices systematically and coherently in a manner that improves language learning.